2021
DOI: 10.3390/met11050686
|View full text |Cite
|
Sign up to set email alerts
|

Warpage Analysis and Control of Thin-Walled Structures Manufactured by Laser Powder Bed Fusion

Abstract: Thin-walled structures are of great interest because of their use as lightweight components in aeronautical and aerospace engineering. The fabrication of these components by additive manufacturing (AM) often produces undesired warpage because of the thermal stresses induced by the manufacturing process and the components’ reduced structural stiffness. The objective of this study is to analyze the distortion of several thin-walled components fabricated by Laser Powder Bed Fusion (LPBF). Experiments are performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…As a result, melt pool size, cooling, and solidification rates increase [33,34], which ultimately affects the microstructure of the part. Due to the higher energy density of laser and slow cooling rates residual stress is generated and results in defects such as warping [35] and loss of corner [10].…”
Section: Disturbance Modelmentioning
confidence: 99%
“…As a result, melt pool size, cooling, and solidification rates increase [33,34], which ultimately affects the microstructure of the part. Due to the higher energy density of laser and slow cooling rates residual stress is generated and results in defects such as warping [35] and loss of corner [10].…”
Section: Disturbance Modelmentioning
confidence: 99%
“…Bugatti et al [13] studied the effect of overhanging surfaces on the formation of internal defects in the laser powder bed fusion-type process. Lu et al [14] assessed the warping for thin-walled structures that are widely used for aeronautical applications. They found that different geometrical characteristics, i.e., the wall thickness, the build height, the wall curvature, and the presence of an open or closed structure, play a key role in the warping occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However, AM is a complicated multi-physics and multi-scale process characterized by several thermal cycles with large temperature gradients as well as melting and solidification phase changes. As a consequence, AM-built products typically show non-uniform microstructure distribution, large residual stresses, thermal distortions, cracks and unsatisfactory mechanical properties [4][5][6][7][8][9][10]. Such drawbacks significantly prevent the extensive application of AM technologies in high-end manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%